Management of Cracked and Weakened Endodontically Treated Teeth Using Fiber-reinforced Composites: A Case Series - de Toubes, Kênia Maria Soares; Meirelles, Fabiana Dantas; Borges, Gilberto Antônio; Mendes, Amauri José Lima; Oliveira, Mauricio Gustavo; Silveira, Frank Ferreira (Iranian Endodontic Journal, 2025)
Restoring endodontically treated teeth (ETT) that exhibit cracks, enlarged roots, or weakened root walls is a frequent challenge in dental practice. The present study describes three cases in which contemporary restorative techniques were employed and suggests that applying Ribbond tape (RT) to ETT can improve fracture resistance and better prevent the propagation of cracks compared with traditional methods. Although extensive in vitro research has been conducted on fiber-reinforced composites, studies evaluating the clinical use and durability of fiber-reinforced composites to restore ETT are limited. This report strictly adhered to the case report (CARE) guidelines, and the treatments were initiated only after signed informed consents were obtained from the patients. Therefore, the old restorations were removed from the teeth that required intervention and composite resin core build-up was created, followed by endodontic treatments or retreatment. Subsequently, the endodontic accesses were reinforced with RT. The protective restorations were performed and bonded. The two-year follow-ups showed that the patients had complete remission of signs and symptoms, and they remain under monitoring. The study emphasizes the importance of internal reinforcement of ETT and strengthening weakened walls with a resin core build-up reinforced with fibers like RT. This approach enhances mechanical retention, inhibit fracture propagation, and establish a strong chemical bond between RT and resin. It is suggested to be a promising strategy for increasing the longevity and strength of the teeth, providing a conservative and effective alternative to traditional methods.